Investigation into changes in inflammatory and immune cell markers in pre-diabetic patients from Durban, South Africa - Nomusa Christina Mzimela; Aubrey Mbulelo Sosibo; Phikelelani Siphosethu Ngubane; Andile Khathi (Journal of Immunotoxicology, 2024)
The prevalence of pre-diabetes is increasing in rapidly urbanizing cities, especially in individuals aged 25 − 45 years old. Studies also indicate that this condition is associated with aberrant immune responses that are also influenced by environmental factors. This study sought to investigate changes in the concentration of immune cells and select inflammatory markers in patients with pre-diabetes in Durban, South Africa. Blood samples collected from King Edward Hospital, after obtaining ethics approval, were divided into non-diabetic (ND), pre-diabetic (PD) and type 2 diabetic (T2D) using ADA criteria. In each sample, the concentration of immune cells and select inflammatory markers were determined. The results showed a significant increase in eosinophil and basophil levels in the PD group as compared to the ND group. Compared to ND, the PD and T2D groups had significant increases in serum TNFα, CD40L and fibrinogen concentrations. Additionally, there were decreases in serum CRP, IL-6, and P-selectin in the PD group while these markers increased in the T2D group. These findings were indicative of immune activation and highlight the impact of pre-diabetes in this population. More studies are recommended with a higher number of samples that are stratified by gender and represent the gender ratio in the city.